Bibliometric research in the field of artificial intelligence. Issue 1 (April 2021) - Tu, Wenyan; Fang, Ji; Fangyu,; Jiao,; Ci, Yutong
Abstract: This paper analyzes the development trend of global artificial intelligence from the perspective of bibliometrics. From the publishing trend, the number of papers published in the field of artificial intelligence is growing rapidly. China and the United States are among the top countries in the output of scientific research papers, and India has the fastest cumulative growth rate. In the research direction, the research on computer vision, image, deep learning and neural network is the research hotspot in recent years.